PENINGKATAN KAPASITAS SEKOLAH DALAM PENGELOLAAN PENDIDIKAN INKLUSIF MELALUI MANAJEMEN YANG ADAPTIF DAN PARTISIPATIF PADA SMA/SMK DI KABUPATEN SAMPANG - Hidayati, Nurul; Badiah, Lutfi Isni; Jauhari, Muhammad Nurrohman (Kanigara, 2026)
Abstract Inclusive education is a strategy to guarantee the right of every citizen to receive quality education without discrimination. However, the implementation of inclusive education at the high school/vocational high school level still faces various challenges, particularly in school management, policy development, and coordination between stakeholders. This community service activity aims to improve the capacity of principals and teachers in managing inclusive education through adaptive and participatory management. The activity was carried out through a collaboration between the Special Education Study Program and the East Java Provincial Education Office at SMAN 2 Sampang. The activity involved 30 participants, consisting of principals and teachers of inclusive high schools/vocational high schools, as well as special needs teachers in Sampang Regency. The methods used included training, workshops, group discussions, and mentoring in developing inclusive school programs. The results of the activity showed an increase in the average score of participants from 63.5 in the pre-test to 84.2 in the post-test, an increase of 32.6%. This activity demonstrates that systematic mentoring can improve schools' capacity to manage inclusive education more effectively and sustainably.